Does Import Competition Induce R and D Reallocation? : Evidence from the U.S. - Xu, Rui (IMF Working Papers; Working Paper ;, 2017)
We analyze the impact of rising import competition from China on U.S. innovative activities. Using Compustat data, we find that import competition induces R and D expenditures to be reallocated towards more productive and more profitable firms within each industry. Such reallocation effect has the potential to offset the average drop in firm-level R and D identified in the previous literature. Indeed, our quantitative analysis shows no adverse impact of import competition on aggregate R and D expenditures. Taking the analysis beyond manufacturing, we find that import competition has led to reallocation of researchers towards booming service industries, including business and repairs, personal services, and financial services.